Comparación de funcionalidades de las plataformas Ecommerce Pardux y Shopify, para el uso en el sector agro veterinario, en la ciudad de Babahoyo - Guerrero Torres, Camilo Javier (2025)
This case study analyzes and compares the functionalities of the e-commerce platforms PARDUX and Shopify, evaluating their applicability in the agro-veterinary sector in the city of Babahoyo. The research focuses on key aspects such as ease of use, customization, inventory management, payment methods, marketing tools, and scalability. A descriptive-comparative methodology is employed, based on practical tests and interviews with key users in the sector. The results highlight the strengths and limitations of each platform, providing recommendations for selecting the most suitable solution according to the specific needs of the agro-veterinary business. This analysis aims to promote the strategic adoption of digital technologies to optimize management and commercialization in the sector.